Sistem Aplikasi Rental Mobil Berbasis Web Untuk Optimalisasi Armada - Pawestri, Cantika Risky Ramdhana; Putro, Otto Santoso (Politeknik Indonusa Surakarta, 2023)
This research discusses the development and implementation of a web-based car rental system as an effective solution to increase efficiency and accessibility in the car rental industry. This system is designed to provide users with the convenience of ordering, managing and tracking vehicle status online. The car rental business has several business processes, including the car ordering process, payment, returns and order cancellation. There are still problems encountered in some of these business processes, where manual bookkeeping systems require more time to process data, search for data, and are susceptible to damage. Nowadays, technology is developing rapidly, changing the lifestyle of people who want a simple, easy to understand, fast to access and flexible system that can be accessed anywhere. This information system was built using the PHP (Hypertext Preprocessor) programming language and uses MySql as the database. By building this car rental system website, it is hoped that it can overcome existing problems such as all transaction processes and car ordering data processing.